Relationship Between Parenting Patterns With Attention Deficit Hyperactivity Disorder In Preschool Children In Kindergarten - Nani Surtinah; Tutiek Herlina; Suparji Suparji; Alvyana Indrajitha (Aloha International Journal of Health Advancement (AIJHA), 2021)
Children affected by Attention-Deficit/Hyperactive Disorder (ADHD) are often given labels that can affect the formation of children's self-concepts. If the situation is not handled properly in childhood, the problem will peak in adolescence. The purpose of the study was to determine the relationship between parenting/caregivers with ADHD in preschool children at Panca Bakti Kindergarten, Selosari, Magetan Regency. This type of analytic research with cross-sectional. Research variables ADHD and parenting. The research population is all parents/caregivers who have preschool children in TK Panca Bakti Selosari, Magetan Regency totaling 39 people. The data were collected by interview using questionnaires. Data analysis using Chi-Square test Children affected by Attention-Deficit/Hyperactive Disorder (ADHD) are often given labels that can affect the formation of children's self-concepts. If the situation is not handled properly in childhood, the problem will peak in adolescence. The purpose of the study was to determine the relationship between parenting/caregivers with ADHD in preschool children at Panca Bakti Kindergarten, Selosari, Magetan Regency. This type of analytic research with cross-sectional. Research variables ADHD and parenting. The research population is all parents/caregivers who have preschool children in TK Panca Bakti Selosari, Magetan Regency totaling 39 people. The data were collected by interview using questionnaires. Data analysis using Chi-Square test α = 0.05. The results showed that the authoritarian parenting style was 13 people (38.5%), democratic parenting was 26 people (61.5%). Children with a high risk of ADHD 15 people (38.5%), not at risk 24 people (61.5%). Based on data analysis using the Chi-Square test, the results obtained p-value = 0.000 which means H0 is rejected. There is a relationship between parenting/caregivers with attention-deficit/hyperactive disorder in preschool children at Panca Bakti Selosari Kindergarten, Magetan Regency. Parents who apply authoritarian parenting will have a high risk of causing ADHD in children, so it is recommended that parents/caregivers apply democratic parenting.The results showed that the authoritarian parenting style was 13 people (38.5%), democratic parenting was 26 people (61.5%). Children with a high risk of ADHD 15 people (38.5%), not at risk 24 people (61.5%). Based on data analysis using the Chi-Square test, the results obtained p-value = 0.000 which means H0 is rejected. There is a relationship between parenting/caregivers with attention-deficit/hyperactive disorder in preschool children at Panca Bakti Selosari Kindergarten, Magetan Regency. Parents who apply authoritarian parenting will have a high risk of causing ADHD in children, so it is recommended that parents/caregivers apply democratic parenting. Keywords: Parenting, ADHD, Preschool Children